SISTEM INFORMASI KEBERADAAN BESI BEKAS DI MASYARAKAT BERBASIS ANDROID - Maryam Pomalingo; Rampi Yusuf; Roviana H Dai (Diffusion: Journal of Systems and Information Technology, 2021)
AbstractIron waste is an object that can be reused for its use value by recycling. To get to the recycling process, iron waste is collected by scrap metal collectors from various areas or various places, then sent to scrap metal dealers to be collected and sent to scrap metal recycling factories. The collectors collect scrap metal to serve as something that has economic value. In editioon, collectors need scrap metal not to be produced but seek and receive scrap metal sales, which will be resold to larger collectors with a higher selling price. The problem that occurs is the difficulty for collectors to locate the presence of scrap metal in the community. Moreover, Another obstacle is that people are still confused about how to infrom scrap metal collectors about the availability of scrap metal in their place. Trus, this research aim to facilitate the collectors to find the location of scrap metal in the community. This system also eases the community to obtain information about the location where the collectors are. The system development method used is the Waterfall method using the PHP programming language and MSQL database.Keywords: Scrap Metal, Waterfall.